Investigation of Cystic Echinococcosis Knowledge Levels of Animal Breeders and Butchers in Ardahan Province in Türkiye - Edanur Gündüz Alan; Nilgün Aydın (Türkiye Parazitoloji Dergisi)
Objective: The objective of this study was to ascertain the knowledge level of animal breeders and butchers regarding cystic echinococcosis (CE) in the Ardahan province and its districts situated in the Eastern Anatolia Region of Türkiye. Additionally, the study aimed to identify the potential risk factors that may contribute to the occurrence of the disease. Methods: The research was conducted between November 2021 and May 2022. A total of 402 animal breeders and 23 butchers participated in the survey. In order to ascertain the extent of awareness regarding CE, a series of multiple-choice questions were administered in a face-to-face setting. Results: Upon evaluation of the data obtained from the research in a socio-demographic context, it shows that people’s awareness of CE increases with age, and women have the most knowledge on this subject (45.85%). A total of 71.76% (305/425) of participants reported owning a dog. Of these, 48.52% (148/305) typically feed their dog food waste. Additionally, 58.03% (177/305) of dog owners do not regularly take their dogs to the vet. The animals were slaughtered by the participants (53.65%; 228/425), and the infected organs found during slaughter were destroyed by deep burial (72.81%; 166/228). The majority of participants (93.41%; 397/425) expressed a desire to gain further insight into the subject. Conclusion: It was thus established that the districts and province of Ardahan are deficient in the availability of information regarding CE among animal breeders and butchers. It was therefore concluded that the inhabitants of the aforementioned region should be made aware of CE and other zoonotic diseases prevalent in the Ardahan province.